The role of car rental business in travel and tourism industry: A Case study of rent a car companies in Lefkada Island - Kalli, Sofia; Avramopoulos, Avraam (International Conference on Business and Economics - Hellenic Open University, 2023)
The present research refers to the role of car rental in the travel industry with a case study on the island of Lefkada. The agencies in the car rental industry have received a great deal of attention in recent years, due to the fact that they have shown immense growth in and out of Greece. In Greece, the car rental industry is most often associated with tourism as it presents the largest turnover of tourists-customers. In the present paper, rent-a-car agencies in the island of Lefkada are canvassed in the literature and research field with the aim of drawing conclusions in relation to their basic features and the quantitative and quality depiction of their workforce. Regarding the research process, a quantitative and qualitative research was carried out. The main tool used in the quantitative research was the questionnaire which was distributed to agencies operating in the field of the car rental industry in the island of Lefkada. The tool of the qualitative research was the interview, which took place in three agencies through face-to-face meetings with their executives. The results indicated that the course of the Greek car rental market, in recent years, is on the rise, which creates a positive climate for the development and progress of the industry. Finally, certain suggestions for future research based on the conclusions are the study on European Funds and NSRF programs for the purchase of electric cars and the simplification of procedures, i.e. the automatization of most actions such as online check. JEL Classifications: L83, L91, M21 Key words: short-term vehicle leases, vehicle rental, types of vehicle leases, management of car rental agencies.